Minimal hepatic encephalopathy is associated with expansion and activation of CD4+CD28−, Th22 and Tfh and B lymphocytes - Alba Mangas-Losada (Nature Portfolio, 2017)
Abstract Peripheral inflammation acts synergistically with hyperammonemia in inducing neurological alterations in cirrhotic patients with minimal hepatic encephalopathy (MHE). We hypothesized that appearance of MHE would be associated to some specific qualitative change in peripheral inflammation. The aim of this work was to characterize the changes in peripheral inflammation associated to appearance of MHE. We analyzed it by immunophenotyping and cytokine profile analysis, in cirrhotic patients without or with MHE and controls. The main alterations associated specifically with MHE are: 1) increased activation of all subtypes of CD4+ T-lymphocytes, with the increased expression of CD69; 2) increased amount of CD4+CD28− T lymphocytes, associated with increased levels of CX3CL1 and of IL-15; 3) increased differentiation of CD4+ T lymphocytes to Th follicular and Th22; 4) increased activation of B lymphocytes and serum IgG. This study has identified some specific alterations of the immune system associated with appearance of the neurological alterations in MHE patients.